2019
DOI: 10.1093/jas/skz077
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in residual feed intake is associated with body composition, behavior, rumen, heat production, hematology, and immune competence traits in Angus cattle1

Abstract: is gratefully acknowledged. Brad Walmsley generously provided the equations used for calculating body composition. One of us (J.I.V.) was supported by an Australian Government scholarship funded by the Australian Agency for International Development and by the National Institute for Agricultural Research (INIA Uruguay).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
(54 reference statements)
3
15
2
Order By: Relevance
“…Studies to date in growing cattle indicate that the number of feed events per day explained an additional 5.7 to 6.0 percentage points of the variability in DMI over and above that already explained by MBW, ADG, and backfat depth ( Durunna et al, 2011 ; Herd et al, 2019 ); this is less than the 9.2 percentage point improvement observed in the present study for MEI. Additionally, in steers fed a high energy finishing diet, Durunna et al (2011) reported an increase in R 2 from 54% to 64% when both feeding time per day and number of feed events per day were included in a model with DMI as the dependent variable; this is similar to the calculated increase from 53% to 67% for the R 2 of the MEI model in the present study.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Studies to date in growing cattle indicate that the number of feed events per day explained an additional 5.7 to 6.0 percentage points of the variability in DMI over and above that already explained by MBW, ADG, and backfat depth ( Durunna et al, 2011 ; Herd et al, 2019 ); this is less than the 9.2 percentage point improvement observed in the present study for MEI. Additionally, in steers fed a high energy finishing diet, Durunna et al (2011) reported an increase in R 2 from 54% to 64% when both feeding time per day and number of feed events per day were included in a model with DMI as the dependent variable; this is similar to the calculated increase from 53% to 67% for the R 2 of the MEI model in the present study.…”
Section: Discussioncontrasting
confidence: 87%
“…Of the studies that have explicitly reported phenotypic correlations between feeding behavior traits and both performance and efficiency traits in a relatively large cohort of cattle ( Robinson and Oddy, 2004 ; Nkrumah et al, 2007 ; Lancaster et al, 2009 ; Kelly et al, 2010 ; Schwartzkopf-Genswein et al, 2011 ; Lin et al, 2013 ), the present study is one of the largest. Furthermore, there is a paucity of studies ( Kelly et al, 2010 ) that have reported the repeatability estimates for feeding behavior traits in cattle using mixed models methodology, and few studies ( Durunna et al, 2011 ; McGee et al, 2014 ; Herd et al, 2019 ) have calculated the contribution of different feeding behavior traits to the variation in either DMI or MEI. There is also a paucity of studies ( McGee et al, 2014 ) reporting correlations at both the feed event level and meal level with performance and efficiency traits in the same cohort of cattle; moreover, information on correlations between feeding behavior and both RG and RIG are apparently nonexistent.…”
Section: Discussionmentioning
confidence: 99%
“…This result was unexpected however we are unable to compare to other studies as to the best of our knowledge this is the first paper to report a relationship between RWLC and temperament traits. We found no relationship between RFI and temperament when measured as chute or exit score, this is consistent with Herd et al (2019) who reported a negative correlation between RFI and temperament when measured as flight score. The presence of a relationship between exit score and RLWC demonstrates a relationship between temperament and some aspect of feed efficiency.…”
Section: Figure 1 Potential Sites Of Action For Phytoestrogens In the Reproductive Processes In Sheepsupporting
confidence: 91%
“…At 48 h incubation, methane production tended be greater (5.0 ± 0.59 v 3.7 ± 0.56 mL, P = 0.07) for Low-RFI-f-EBV than High-RFI-f-EBV. This tendency for greater methane production/unit digesta from more efficient cattle at 48 h incubation is consistent with the results of Herd et al (2019) and greater digestion in the rumen of more efficient animals, but needs to be married with data on rumen volume to provide a fuller picture of RFI effects on daily methane emission. Further studies should include rumen characteristics between cattle varying in RFI-f-EBVs grazing pastures of differing quality and availability and at different stages of the production cycle.…”
Section: Referencesupporting
confidence: 71%
See 1 more Smart Citation